Oral Health Effects of Antipsychotic Agents on Residents in a Psychiatric Facility in Medan, Indonesia - Fialdy Josua Pattiradjawane; Sondang Pintauli (Journal of Indonesian Dental Association, 2021)
Introduction: Antipsychotic agents consumed by patients with mental illnesses can have adverse effects on the oral health. These effects include altering the composition and flow of saliva, thus reducing its protective capabilities, which, in turn, increases the risk of caries. Objective: This study aimed to analyze the effects of antipsychotic drug use on salivary pH, salivary flow rate, and caries incidence on psychiatric inpatients in Pemenang Jiwa Foundation, Medan, Indonesia. Methods: This was an observational analytical study with a cross-sectional design. The sample population comprised male and female residents in Pemenang Jiwa Foundation. The population was selected through purposive sampling, which yielded 51 participants. Usage of antipsyhotics were categorized based on the duration (3-6 months, 6 months to 3 years, >3 years) and the number of daily drug consumption (1, 2, 3, >3). Oral manifestations evaluated were salivary flow rate, pH, and DMFT. Chi-square and Fisher’s exact tests were used to analyze the association between the consumption of antipsychotic agents and salivary pH, salivary flow rate, and caries incidence. Results: There were 28 females and 23 males with a mean age of 41 years old were included in the study. More than half of the respondents (51%) had consumed antipsychotic medications daily for between 6 months and 3 years. Fewer than half of the respondents (45.1%) consumed more than three types of antipsychotic medications. There was a significant association between the quantity of antipsychotic agents consumed daily and salivary pH (p=0.007), salivary flow rate (p=0.0001), and caries incidence (p=0.006). Only the duration of antipsychotic drug use and not the number of antipsychotic drugs consumed daily was associated with salivary pH (p=0.014). Conclusion: The quantity and duration of use of antipsychotic agents affects salivary pH, salivary flow rate, and caries incidence.